Back Pain, Neurogenic Symptoms, and Physical Function in Relation to Spondylolisthesis among Elderly Men - Denard, Patrick J. (2010)
BACKGROUND CONTEXT: Degenerative spondylolisthesis is a presumed cause of back pain. Previous studies of spondylolisthesis and back pain included only women or combined results for men and women. Comparisons of the frequency of back pain, neurogenic symptoms, and functional limitations specifically among elderly men with and without spondylolisthesis are needed. PURPOSE: To determine associations of prevalent spondylolisthesis with back pain symptoms, neurogenic symptoms, and functional limitations among elderly men. Study Design/ Setting: Cross-sectional epidemiologic study conducted within the Osteoporotic Fractures in Men (MrOS) cohort. The MrOS cohort is comprised of 5,995 community dwelling men ages ≥65 years who were recruited at 6 US academic medical centers. Extensive self-reported data and lumbar spine radiographs were obtained for all MrOS participants at baseline. PATIENT SAMPLE: For this study, 300 men were selected at random specifically for the evaluation of spondylolisthesis on the baseline spine radiographs. OUTCOME MEASURES: Standardized questionnaires were used to assess self-reported back pain, leg pain (radiculopathy), lower extremity numbness (paresthesias) and lower extremity weakness occurring in the past 12 months, and to ascertain current difficulty with activities of daily living. METHODS: In the present study, radiographic spondylolisthesis was classified as forward slip of ≥5%. Prevalence of back pain, neurogenic symptoms and difficulty with activities of daily living were compared between men with and without spondylolisthesis using chisquare or Fisher’s exact tests. RESULTS: Spondylolisthesis was present among 92 (31%) men. Among men with and without spondylolisthesis, back pain (63% vs. 67%, p=0.46) and moderate/severe back pain (41% vs. 38%, p=0.76) were reported with similar frequency. Men with spondylolisthesis more often reported radiculopathy (33% vs. 22%, p=0.06), paresthesias (18% vs. 11%, p= 0.10) and weakness (18% vs. 9%, p=0.02) in the lower extremities; as well as difficulty walking 2-3 blocks (21% vs 11%, p=0.03), doing their own shopping (8% vs 2%, p=0.04), and getting in/out of a car (14% vs 6%, p=0.03), compared to men without. CONCLUSIONS: Among elderly men, spondylolisthesis was associated with neurogenic symptoms and lower extremity functional limitations; however, spondylolisthesis was not associated with a higher likelihood of back pain in this population.